Proyectos pedagógicos de aula: una mirada conceptual de la práctica pedagógica investigativa de profundización - Fagua, Nelson Guerrero (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The article explores and reflects on the classroom pedagogical projects, which were applied in different educational settings by teachers of the pedagogical practice re- search of deepening. Those projects show the importance of developing pedagogi- cal interventions, in order to make up for needs and improve educational processes in a didactic way. This research process is carried out in the period 2015-2016 in the Regional Center for Distance Education Cread of Sogamoso. For the construction of this article, a series of concepts and authors are considered, that make it possible to deal with issues such as; Pedagogical practice, projects, classroom pedagogical projects, and all the importance within the Teaching, besides, the procedures of providing innovative ideas. The systematization process was carried out through the practice reports made by each student.